Efficiency and productivity assessment of wind farms - Vaz, Clara B. (2018)
This study develops a framework to provide insights regarding the performance of the farms of an energy player in the Portuguese wind sector. The focus of the wind farm performance assessment is on the operating stage which corresponds to the electrical energy generation process, during 2010 and 2011. In a first stage, Data Envelopment Analysis is used to measure the efficiency of wind farms in generating electrical energy from the resources available and nondiscretionary variables. This analysis enables the identification of the best practices of the efficient farms which can be emulated by inefficient ones. In a second stage, changes in wind farms productivity are investigated using Malmquist index. Bootstrap procedures are applied to obtain statistical inference on the efficiency estimates. We conclude that almost all farms decreased overall productivity levels, mainly due to the decline in the productivity levels of the frontier, which is in accordance with the decrease in wind availability observed in 2011.